Prenuptial medical exams in debate: a proposed eugenic intervention in Brazil, 1910-1940 - Peixoto, Priscila Bermudes [UNESP] (Fundaco Oswaldo Cruz, 2016)
This text results from research undertaken for a master's degree that focused on the proposed introduction of prenuptial medical exams in the early 1900s in Brazil. This was strongly defended by Brazilian eugenicists as a much-needed means of bringing about the racial improvement of the population. The exam would help prevent the marriage and reproduction of individuals considered degenerate or inferior, seen as inadequate for the eugenic development of future generations. The debate in Brazil between doctors and intellectuals who supported the introduction of a law that would make a prenuptial medical exam mandatory is analyzed, as are the controversies and objections voiced by its critics, ultimately helping ensure it was not adopted in the country.
Keywords: eugenics; prenuptial exam; medicine; marriage; reproduction